An unusual case of ruptured noncommunicating rudimentary horn pregnancy at 10 weeks - Pande, Kiran; Yadav, Angela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Unicornuate uterus with noncommunicating rudimentary horn occurs due to incomplete fusion of mullerian ducts. Pregnancy in this horn is a rare phenomenon usually resulting in rupture during second trimester of pregnancy. Prerupture diagnosis of pregnancy in rudimentary horn with ultrasonography is technically difficult, with sensitivity of 30%. We report a case of ruptured non-communicating rudimentary horn at 10 weeks 3 days in a woman. She had a routine USG before pregnancy in which diagnosis was missed. Later she presented to emergency in shock, with massive hemoperitoneum and ruptured horn. So, a high index of suspicion is required to save this catastrophic event and associated maternal morbidity and mortality.